Prevalence and Predictors of Depression Among Drug-Sensitive Tuberculosis Patients - A Cross-Sectional Study - Deepak Sharma; Naveen K. Goel; Ajeet Sidana; Kawaljeet S. Sandha; Mamta Bishnoi (Wolters Kluwer Medknow Publications, 2024)
Background: According to World Health Organization, India is a high tuberculosis (TB) and depression burden state. The risk of depression is higher among TB patients. Therefore, it is vital to focus on the mental well-being of TB patients. Objective: The present study aimed to determine the prevalence and predictors of depression among drug-sensitive TB patients in Chandigarh city. Methods: A cross-sectional study was conducted among 305 TB patients. Trained investigators administered Patient Health Questionnaire 9 to screen for depression. Data analysis was done using Epi info software for windows. Results: The prevalence rate of depression among drug-sensitive TB patients was 7.2%. Current nonworking individuals were more likely to be depressed than their counterparts (OR = 3.7 (1.2-10.9)). Conclusion: Around one-tenth of the TB patients were suffering from depression. This necessitates physicians to regularly screen TB patients for depression and manage accordingly, which will help improve treatment adherence and outcome.